Assessing the influence of teaching strategies, accessibility of equipment, and technological influence on students’ contentment with online education using multiple linear regression / Mohd Azry Abdul Malik ... [et al.] - Abdul Malik, Mohd Azry; Md Noor, Mohd Rahimie; Sabri, Nur Ain Natasha; Mazlan, Mastura Nabilah; Rohazien, Nurain Aqilah; Mohamad, Siti Nur Adibah; Amran, Amni Aniqah; Sahroni, Mohamad Norzamani; Ghazali, Jasrul Nizam (Unit Penerbitan UiTM Kelantan, 2024)
The educational landscape has undergone a substantial transformation in recent years due to the widespread adoption of online education. Educational institutions have embraced digitalisation and incorporated online learning as a crucial tool for teaching and learning process. This study aims to measure the relationship between the lecturers’ teaching strategies, the accessibility of equipment, and technological influence on students’ contentment with online education. Additionally, the study aims to compare students’ contentment levels of male and female students with online education. 150 participants enrolled in the Diploma in Mathematical Science programme at a prominent higher education institution in Kelantan were involved in this study. Data collection is done through self-administered questionnaires, and data analysis employed ordinary least squares estimation. The findings reveal significant relationships between teaching strategies, technological influence, and students’ contentment with online education. Notably, no discernible differences in contentment levels were observed between male and female students. The study offers valuable insights for higher education administrators and policymakers seeking to enhance students’ contentment with online education.